The Outcome of Shock Wave Lithotripsy (SWL) in the Treatment of Urinary Stone Disease: 115 Cases in SOMCH (Bangladesh Journal of Urology, 2022)
Purpose: Urinary stone disease is a systemic metabolic and recurrent disease. It is the third most common disease of the urinary tract. Urolithiasis affects 4%-15% of the world population and this is increasing. Treatment of urinary stone disease moved dramatically from open operative procedures to endoscopic, minimally invasive, and noninvasive methods. The introduction of shock wave lithotripsy (SWL) has revolutionized the treatment of urinary stones with the concept of disintegration of stones. The present study aims to evaluate the outcome of SWL in the treatment of urinary stone disease.Methods and Materials: This retrospective observational study was conducted in the department of urology, SOMCH from June 2019- to March 2021. Renal stone